COMPLICATIONS OF DENTAL IMPLANTATION IN OVERWEIGHT PATIENTS - Panahov, N.A.; Safarov, M.A.; Mammadov, F.Y. (World of Medicine and Biology, 2024)
The purpose of the study was to assess the condition of periodontal tissues and oral microflora after dental implantation in obese individuals. Clinical and microbiological assessment of complications of dental implantation was carried out among 15 patients with obesity and peri-implant mucositis (Group I), 15 patients with metabolic disorders and mild dental peri-implantitis (Group II) and in Group III (20 similar somatic patients without pronounced pathological changes in the periodontal tissues and peri-implant zone). Obesity against the background of intensive deposition of soft dental plaque and further formation of hard dental deposits in the area of the orthopedic structure planted on the implant in somatic patients with peri-implant mucositis and peri-implantitis contributed to a reliable increase (P
Keywords: dental implants; peri-implant disease; perimucositis; periimplantitis; microbiota